Analisis implementasi pajak reklame berdasarkan Peraturan Daerah No. 2 tahun 2011 (Studi pada Badan Pendapatan Daerah Kota Manado) - Siahaan, Josua Jonathan; Warongan, Jessy D. L.; Tangkuman, Steven J. (Yayasan Widyantara Nawasena Raharja, 2024)
Advertising tax is a fee that must be paid to obtain a license to organize advertising. The purpose of this study is to analyses the implementation of local regulations on local taxes that deal with advertising tax. The research method is qualitative. Data sources are primary and secondary data. The data collection procedure uses interview, observation, and documentation methods. The findings of this study show. (1) The identification of the name, object, subject and taxpayer is in accordance with the Regional Regulation No. 2 of 2011. (2) The determination of the amount of tax due for each advertising tax payer was based on the calculations provided for in Regional Regulation No. 2 of 2011, i.e. at a rate of 25% of the amount of payments made by the tax payer. (3) The Regional Tax Invoice Letter was issued in accordance with Regional Regulation No. 2 of 2011. (4) The collection of the advertising tax has been established in accordance with the Regional Regulation No. 2 of 2011.